The Professional Diplomat - Harr, John Ensor (Princeton, NJ : Princeton University Press, 2015)
The role of the Foreign Service Officer of the United States altered radically during and after World War II. John Harr, who served as a staff member of the Commission on Foreign Affairs Personnel in 1962 and as Director of the Office of Management Planning in the State Department for four years, describes the changes and the response of the Foreign Service Corps to them. He provides a direct approach to the understanding of the professional diplomat and of the pervasive force of professionalism in modern American society. He also outlines managerial strategy to meet the growth challenge of the future.Originally published in 1969.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Acknowledgment -- Tables and Figures -- Abbreviations -- Chart, Organization of the Department of State -- General Schedule for Civil Service, Foreign Service Officer, Foreign Service Reserve, and Foreign Service Staff -- Introduction -- Part I. The Background and Forces of Change -- 1. The Profession: A New Diplomacy? -- 2. The System -- 3. The Organization -- Part II. The Professional Group -- 4. Composition of the Corps -- 5. Social Origins and Characteristics -- 6. Characteristics, Norms, Attitudes -- 7. Change and the Profession -- 8. Coordination and Leadership -- Part III. Conclusion -- 9. A Managerial Strategy for the Future -- Appendix I. Methodological Appendix -- Appendix II. Documents -- Bibliography -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Diplomatic and consular service, American; POLITICAL SCIENCE / International Relations / Diplomacy